UPAYA MENGATASI KEKERASAN DALAM RUMAH TANGGA (KDRT) MELALUI PENDEKATAN KONSELING KELUARGA DI LEMBAGA P2TPAKK REKSO DYAH UTAMI YOGYAKARTA [THE EFFORTS TO OVERCOME DOMESTIC VIOLENCE (KDRT) THROUGH FAMILY COUNSELING APPROACH AT INSTITUTE OF P2TPAKK REKSO DYAH UTAMI YOGYAKARTA] - Jatmiko, Anggi (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2022)
The background of this research is that there are still many cases of violence that occur in the household, but those who are involved in it have not been able to solve their own problems. So it requires a third party to help solve the problem at hand. This study uses qualitative research methods with descriptive analysis research type. The data collection method used observation, interviews, and documentation with the research subject being a family counselor at the Institute of P2TPAKK Rekso Dyah Utami. The results showed that family counselors used a family counseling approach in dealing with cases of domestic violence with various efforts, starting from listening, exploring, to the counseling process. It is hoped that the existence of family counseling can help couples in solving their problems and rebuilding their families who had experienced a crisis.